RXPERT: A Decision Support Expert System for Drug Product Interchangeability Assessment - Greer, Marianne L. (1989)
A knowledge-based expert system has been developed to support human decision makers who assess drug products for inclusion in the Saskatchewan Formulary. Formulary inclusion and deletion decisions are made by two committees. The Drug Quality Assessment Committee (DQAC) performs the initial clinical evaluation and makes recommendations to the Formulary Committee (FC). The FC then considers the practical and administrative implications of the DQAC recommendations and makes recommendations to the Minister of Health. The RXPERT Formulary Advisor is designed to model and support the decision processes of the two committees, primarily in the area of interchangeability among chemically equivalent products. Committee meeting minutes were analyzed and members observed and interviewed to suggest rules which form the basis of the RXPERT advisor. The prototype expert system attempts to model committee decision making, based on multiple experts with overlapping, but distinctly focussed, areas of expertise. The major anticipated contribution is screening of routine decisions to ensure efficient and consistent assessment and free experts' time for more complex cases.